First Report on the Publication and Conservation of the Tomb of Ramesses III in the Valley of the Kings (KV 11). Issue 1 (June 2018) - Weber, Anke
The tomb of Ramesses III (KV 11) in the Valley of the Kings is one of the archaeological sites of ancient Egypt that has received very little attention from the scientific community. The tomb was open to the public for a long time and is in danger of quick deterioration. The site was closed from August 2016 until October 2017 for the installation of new walkways, glass panels, and an improved lighting system. The Ramesses III (KV 11) Publication and Conservation Project now aims to record, document, and preserve the entire tomb. This article is a first report on the planned publication and conservation of the tomb of Ramesses III (KV 11) in the Valley of the Kings. Like so many other tombs in the wadi, it presents the astonishing case of a tomb that has been known for a long time but was never thoroughly studied. In the following, we present the research aims of the newly formed Ramesses III (KV 11) Publication and Conservation Project 1 as well as the preparatory work that has been undertaken by our team members. All observations and notes were made over the last six years during short campaigns, partly within the framework of a previous research project, 2 which constitutes the basis of preliminary work in KV 11. The article focuses on the historical background of the tomb, its research history, including former investigators and concessions, supposed causes of destruction, suggestions for preservation, and procedures for research and documentation. We present the main problems we have to deal with at the outset of the project and describe the methods we propose to adopt. Further annual reports on the progress and first results of our work in order to preserve this important site of Egypt's cultural heritage will follow in due course.